A laryngeal closure technique for the treatment of patients with head and neck cancer. Issue 2 (31st January 2019) - Furukawa, Tatsuya; Komatsu, Hirokazu; Fujio, Hisami; Kojima, Yasutaka; Morita, Naruhiko; Teshima, Masanori; Shinomiya, Hirotaka; Morimoto, Koichi; Otsuki, Naoki; Kano, Makoto; Nibu, Ken‐ichi
Abstract : Background: In 2008, Kano developed a new laryngeal closure technique (Kano's method) for the treatment of severe aspiration. The aim of this study was to evaluate the safety and efficacy of this technique in patients with head and neck cancer. Methods: Since June 2014 until March 2018, six patients underwent Kano's method for management of severe aspiration after the treatment of head and neck cancers. The anterior parts of the thyroid and the cricoid cartilages were excised widely. The glottis was closed by suturing bilateral vocal folds and reinforced by the sternohyoid muscle. A tracheostoma was created with skin flaps, subglottic mucosal flaps, and stumps of cricoid and trachea cartilages. Results: No severe complications were observed after the surgery. Oral intake improved without developing aspiration. Conclusions: Kano's method can provide satisfactory functional results with minimal invasion for treating severe aspiration after advanced surgery, chemotherapy, and/or chemoradiotherapy, in patients with head and neck cancer. Level of Evidence: 4